Relationship between red blood cell membrane fatty acid composition and dietary fatty acids level in obese adolescents with/without metabolic syndrome - Güneş, Ömer; Soylu, Meltem; İnanç, Neriman and Tascılar, Emre and Sertoğlu, Erdim and Taş, Ahmet and Serdar, Muhittin A. and Özcan, Okan (Progress in Nutrition, 2018)
Background: Dietary lipids may lead to significant changes in the composition of cell membrane structure. Objective: The association between red blood cell (RBC) membrane fatty acid composition and dietary fatty acids intake in obese adolescents with and without metabolic syndrome was investigated. Methods: Ninety-six adolescents (59 obese and 37 lean) were included in the study. The obese subjects were divided into two groups with (n=26, aged 12.3 years ) and without (n=33, aged 12.7 years) metabolic syndrome. The mean age of lean participants was 11.8. The criteria for metabolic syndrome were: 10 <16 age group; BMI ≥ 95th percentile, triglycerides ≥ 150 mg/dL, HDL- C< 40 mg/dL, blood pressure systolic ≥ 130, diastolic ≥ 85 mm Hg, glucose ≥ 100 mg/dL. Subjects with any 3 of these 6 items were accepted with metabolic syndrome. Nutrient intakes were recorded for 3 days by a dietitian. Anthropometric and blood chemistry variables and RBC membrane fatty acid levels were measured. Results: BMI, BMI-SDS, body fat percentage, blood pressure, TG, ALT, insulin, HOMA-IR levels (p<0.001) of obese were significantly higher than lean adolescents whereas HDL-C levels were lower (p<0.001) in obese than lean. Fiber, C22:1 ω-9 MUFA, C20:4 ω-6 PUFA consumption were higher (p<0.05) in obese with metabolic syndrome. Consumption of total ω-3 PUFAs were higher (p<0.05) in obese with metabolic syndrome and in leans than those without the metabolic syndrome. The RBC membrane C16:1 ω-7 fatty acid levels were higher but C20:5 ω-3 levels were lower (p<0.001) in obese. Diet fiber was positively associated with RBC C16:1 ω-7 fatty acid (r=0.239, p<0.05). A positive slight correlation was determined between diet and RBC membrane C20:5 ω-3 (r= 0.200, p= 0.051). Conclusion: Dietary fatty acids affected some anthropometric measurements and blood chemistry. The RBC membrane C20:5 ω-3 slightly correlated with diet C20:5 ω-3.